Typification and characterisation of the pheasant (Phasianus colchicus) game farms in Spain - González-Redondo, P.; García-Domínguez, P. (Spanish Journal of Agricultural Research, 2012)
This research typified and characterised the pheasant (Phasianus colchicus) game farms in Spain using structural and marketing variables. A structured survey was given to 25 private-owned farms in May 2010. A categorical principal components analysis performed to typify the farms yielded two dimensions. First dimension explained 50.5% of the variance and included the variables “number of females in the breeding flock”, and “the farm is of complete-cycle or not”. Second dimension explained 32.3% of the variance and included the variables “age of the farm” and “the farm advertises its activity in the game press”. A cluster analysis differentiated four farm typologies. Farm type 1 included 28% of the farms, being recent (established between 1990 and 2003), complete-cycle and medium-sized (breeding flock of 15 to 300 females), with low advertising activity in the game press and without a hunting preserve. Farm type 2 included 28% of the farms, being the most recent (established between 1994 and 2008), without breeding flock, with low advertising activity, and most have hunting preserve. Farm type 3 included 20% of the farms, being old (established between 1983 and 1992), without breeding flock and with high advertising activity; 40% of them have hunting preserve. Farm type 4 included 24% of the farms, being old (established between 1980 and 1995), complete-cycle and high-sized (breeding flock of 50 to 1,000 females), with high advertising activity; most have hunting preserve. In conclusion, this is an alternative poultry sub-sector consolidated in Spain, despite being only three decades old.